Róise & Frank [videorecording (DVD)] - Moriarty, Rachael; Murphy, Peter (Filmmaker); Ní Neachtain, Bríd; O'Gairbhí, Cillian; Cranitch, Lorcan, 1959-; De Faoite, Ruadhán (Juno Films, 2023)
Róise is still grieving the loss of her husband, Frank, when a mysterious dog shows up at her door. Mildly annoyed by the canine attempting to disrupt her mourning, she attempts to ignore him. But before long, a series of coincidences convince her that somehow this shaggy dog is her husband Frank reincarnated. Soon the dog will win over others in their small town, as well as becoming the unlikely coach to a shy, hurling-loving local boy, before mysteriously disappearing.